MASP-2 Is a Heparin-Binding Protease; Identification of Blocking Oligosaccharides - Talsma, Ditmer T.; Poppelaars, Felix; Dam, Wendy; Meter-Arkema, Anita H.; Vivès, Romain R.; Gál, Peter; Boons, Geert-Jan; Chopra, Pradeep; Naggi, Annamaria; Seelen, Marc A.; Berger, Stephan P.; Daha, Mohamed R.; et al. (Frontiers in Immunology, 2020)
It is well known that heparin and other glycosaminoglycans (GAGs) inhibit complement activation. It is however not known whether fractionation and/or modification of GAGs might deliver pathway-specific inhibition of the complement system. Therefore we evaluated a library of GAGs and their derivatives for their functional pathway specific complement inhibition, including the MASP-specific C4 deposition assay. Interaction of human MASP-2 with heparan sulfate/heparin was evaluated by surface plasmon resonance, ELISA and in renal tissue. In vitro pathway-specific complement assays showed that highly sulfated GAGs inhibited all three pathways of complement. Small heparin- and heparan sulfate-derived oligosaccharides were selective inhibitors of the lectin pathway (LP). These small oligosaccharides showed identical inhibition of the ficolin-3 mediated LP activation, failed to inhibit the binding of MBL to mannan, but inhibited C4 cleavage by MASPs. Hexa- and pentasulfated tetrasaccharides represent the smallest MASP inhibitors both in the functional LP assay as well in the MASP-mediated C4 assay. Surface plasmon resonance showed MASP-2 binding with heparin and heparan sulfate, revealing high Kon and Koff rates resulted in a Kd of ~2 µM and confirmed inhibition by heparin-derived tetrasaccharide. In renal tissue, MASP-2 partially colocalized with agrin and heparan sulfate, but not with activated C3, suggesting docking, storage and potential inactivation of MASP-2 by heparan sulfate in basement membranes. Our data show that highly sulfated GAGs mediated inhibition of all three complement pathways, whereas short heparin- and heparan sulfate-derived oligosaccharides selectively blocked the lectin pathway via MASP-2 inhibition. Binding of MASP-2 to immobilized heparan sulfate/heparin and partial co-localization of agrin/heparan sulfate with MASP, but not C3b, might suggest that in vivo heparan sulfate proteoglycans act as a docking platform for MASP-2 and possibly prevent the lectin pathway from activation.